Open source simulation of fixational eye drift motion in oct scans: Towards better comparability and accuracy in retrospective OCT motion correction - Nau, Merlin A.; Nau, Merlin; Moult, Eric M.; Fujimoto, James G.; Maier, Andreas (Informatik aktuell, 2020)
Point-wise scanning modalities like Optical Coherence Tomography (OCT) or Scanning Laser Ophthalmoscopy suffer from distortions due to the perpetual motion of the eye. While various motion correction approaches have been proposed, the absence of ground truth displacements or images entails a lack of accurate and comparable evaluations. The purpose of this paper is to close this gap by initiating an open source framework for the simulation of realistic eye motion and corresponding artificial distortion of scans, thereby for the first time enabling the community to a) create datasets with accessible ground truth and b) compare the correction of identical motion patterns in data acquired with different scanners or scan patterns. This paper extends previous work on simulation of fixational eye drift via a self-avoiding random walk in a potential to a continuous domain in time and space, allowing the derivation of smooth displacement fields. The model is demonstrated by presenting an examplary motion path, whose properties resemble reported properties of recordings in current literature on fixational eye motion. Furthermore, the artificial distortion of scans is demonstrated by showing a correspondingly distorted image of a virtual raster scan modeled according to the properties of an existing OCT scanner. All experiments can be reproduced and adapted to arbitrary scanner- and raster scan pattern-properties in the publicly available framework. Beyond that, the open source code provides a starting point for the community to integrate extensions like saccadic or axial eye motion.
CRIS-Team Scopus Importer:2020-04-21